On voter competence - Goren, Paul. (New York ; Oxford : Oxford University Press, 2013)
Research shows that most citizens are shockingly uninformed about public affairs, liberal-conservative ideologies, and the issues of the day. This has led most scholars to condemn typical American voters as politically brainless and to conclude that policy voting lies beyond their reach. 'On Voter Competence' breaks sharply from this view. According to Paul Goren, people vote based on abstract policy principles, a practice that has escaped scholars because they have searched for evidence of policy voting in the wrong places.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Voting -- United States; Voting -- United States -- History